An integrated approach to analyzing risk in bioeconomic models. (9th May 2018) - N. Poudel, Biswo; P. Paudel, Krishna
Abstract : Abstract: We provide a new integrated approach to analyzing risk in a setting where both exogenous and endogenous risks are present. We explicitly model these risks to understand their implications to the precautionary principle. We find that, among other things, the increase of exogenous risk in the presence of endogenous risk has a different impact on precaution than the increase in exogenous risk in the presence of only exogenous risk. While the latter is known to decrease precaution, the former unambiguously increases the precaution in the presence of stock effect. Recommendations for Resource Managers: Two kinds of risk are prevalent. Endogenous risk is created by human action. Exogenous risk is created by nature. Endogenous risk can be minimized by taking several actions. If there is only endogenous risk, resource managers should take precaution in extracting the resources. Managers should take precaution in extracting resources if there are both endogenous and exogenous risk and if there is stock effect. Without stock effect, results are ambiguous. If there is only exogenous risk, managers can do nothing. Therefore, managers should allow for the depletion of resources.